ANALISIS JARINGAN AKSES OPTIK UNTUK MENINGKATKAN KUALITAS LAYANAN BTS TELKOMSEL DI PT TELKOM WITEL BANDUNG - Rafika Ratik Srimurni, Rafika Ratik Srimurni; Siti Nur, Siti Nur; Iwan Satriyo Nugroho, Iwan Satriyo Nugroho; Rantiyo, Rantiyo; Muhammad Luthfi Gozali, Muhammad Luthfi Gozali; Mochammad Rafi, Mochammad Rafi (Fakultas Teknik, 2024)
PT Telkom Witel Bandung is committed to providing reliable and quality Internet services in the digital era. With a focus on MBB (Mobile Broadband) & BGES (Business Government Enterprise Services) Units. Optical access network analysis is a focus for improving service quality and maintaining service quality. Quality management, as a systematic approach, is used to understand customer needs and ensure products or services meet expectations. Factors such as quality control, quality assurance, and quality improvement become an integral part of the quality management strategy. Preventive maintenance provides benefits in extending asset life and increasing customer satisfaction. BTS as a telecommunications service, analysis is carried out on Packet Loss (Sending and receiving data packets), Latency (Delay), and Jitter on BTS services. The results show Packet Loss analysis of 0% (Specifications), Latency 470 ms (Under specifications), and Jitter 3 ms (Specifications). Analysis of the causes of high latency using QOS and fishbone diagrams identifies factors such as environment, machines, people and methods. Improvement proposals include device updates, natural disaster risk management and geographic distance, field technician convenience, checking or controlling. Thus, it can be concluded that the application of network analysis and quality management are key steps to improve the quality of Telkomsel BTS services at PT Telkom Witel Bandung. Improvement efforts are expected to optimize service performance and meet customer expectations in this digital era.